2019
DOI: 10.17706/ijeeee.2019.9.1.54-60
|View full text |Cite
|
Sign up to set email alerts
|

The Seven Traits of a Learning Environment: A Framework for Evaluating Mobile Learning Engagement

Abstract: Mobile technology is increasingly used both in and out of school classrooms by students to remain actively engaged in learning and extend their learning. Developments in mobile technology have made it possible to access and interact with learning resources, other learners and teachers in ways not possible just a few years ago. Instructional designers and teachers struggle to maintain understandings of how changes in technology impact student interactions and learning engagement. Instead of focusing on particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
2
Order By: Relevance
“…In such an environment, students increase channels for communication with others, as well as new ways to access and process information. By the very nature of these connections, learning opportunities expand [ 7 ]. The instructor's job is to prepare an environment in which that can happen [ 8 ].…”
Section: Concept Definition and Theoretical Basismentioning
confidence: 99%
“…In such an environment, students increase channels for communication with others, as well as new ways to access and process information. By the very nature of these connections, learning opportunities expand [ 7 ]. The instructor's job is to prepare an environment in which that can happen [ 8 ].…”
Section: Concept Definition and Theoretical Basismentioning
confidence: 99%
“…Dalam dimensi ini, pemanfaatan teknologi cenderung menunjukkan sedikit perubahan pada bagaimana suatu tugas dilakukan dan kemudian diselesaikan. Namun pengaruh penerapan teknologi di dalamnya memungkinkan tugas tersebut diselesaikan dengan lebih efektif dan efisien (Arnold, 2019).…”
Section: Hasil Dan Pembahasan Mengenal Model Samrunclassified
“…Suatu tugas tidak mungkin dapat diselesaikan tanpa pemanfaatan teknologi (Geer et al, 2017). Tahap transformasi juga mendeskripsikan bagaimana penggunaan teknologi dipandang sebagai pengubah hakikat dari pengalaman belajar itu sendiri serta apa yang dipelajari (Arnold, 2019).…”
Section: Hasil Dan Pembahasan Mengenal Model Samrunclassified
“…(4) Redefinition is when students use technology to redefine their tasks. Scholars suggested that this SAMR model should be integrated into developing online learning classes (Arnold, 2019;Pfaffe, 2017;Romrell, Kidder, & Wood, 2014). Therefore, this model was adapted to be used in this study, and it was integrated into the English for Presentation class by providing a suitable online course during this pandemic.…”
Section: The Matrix Modelmentioning
confidence: 99%